Večdisciplinarni pristop kot bistveni dejavnik pametnega in trajnostnega razvoja podeželja - Zavratnik, Veronika (Etnolog. Nova vrsta (Ljubljana), 2020)
The concept of smart villages is connected with rural areas in the European Union and elsewhere around the world, and refers to a complex of environmental, social, economic and other related issues. The article emphasises primarily the importance of a multidisciplinary approach in the understanding of the concept of smart villages and particularly to its applied use. Through selected local examples, it shows the value of different perspectives in the treatment of the relationship between people and the (natural, social, economic, cultural) environment. Through the example of the European project, Smart Villages Interreg Alpine Space, the authors describe a way of cooperation between social sciences and technical/engineering disciplines, drawing attention to the necessity for a wider understanding of digitalisation.
Keywords: digitalizacija; informacijske in komunikacijske tehnologije; lokalne skupnosti; pametne vasi; podeželje; Slovenci; trajnostnost; večdisciplinarnost